2014
DOI: 10.1371/journal.pone.0102602
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-493 Suppresses Tumor Growth, Invasion and Metastasis of Lung Cancer by Regulating E2F1

Abstract: miRNAs have been proposed to be key regulators of progression and metastasis in cancer. However, an understanding of their roles and molecular mechanisms is needed to provide deeper insights for better therapeutic opportunities. In this study we investigated the role and mechanism of miR-493 in the development and progression of nonsmall-cell lung cancer (NSCLC). Our data indicated that the expression of miR-493 was markedly reduced in pulmonary carcinoma. The ectopic expression of miR-493 impaired cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
6
41
0
Order By: Relevance
“…1). Consistent with other cancers, the relationship between cancer progression and the overexpression of these genes was observed (36)(37)(38)(39)(40)(41). Recently, Santos and colleagues (42) also reported that the increased tumor recurrence and progression in patients with NMIBC is associated with increased E2F and EZH2 expression.…”
Section: Discussionsupporting
confidence: 65%
“…1). Consistent with other cancers, the relationship between cancer progression and the overexpression of these genes was observed (36)(37)(38)(39)(40)(41). Recently, Santos and colleagues (42) also reported that the increased tumor recurrence and progression in patients with NMIBC is associated with increased E2F and EZH2 expression.…”
Section: Discussionsupporting
confidence: 65%
“…Our data collectively suggest that miRNAs are evolutionarily conserved regulatory noncoding RNAs that directly control expression of ∼60 % of the human genome [5]. Increasing evidence supports the involvement of altered miRNA expression in the initiation and progression of NSCLC [22,23]. Recently, abnormal expression of miR-342-3p was reported in several human diseases.…”
Section: Discussionsupporting
confidence: 56%
“…It was reported that miR-493 inhibited the formation of metastatic foci and thus prevented liver metastasis of colon cancer cells (33). miR-493, was found to be reduced in lung cancer cells and tissues and to suppress cell invasion and proliferation by blocking E2F1 (34). miR-493 inhibited cell invasion and migration by blocking FZD4 and RhoC in bladder cancer (35).…”
Section: Discussionmentioning
confidence: 96%